Impacts of Dietary Phytochemicals in the Presence and Absence of Pesticides on Longevity of Honey Bees (Apis mellifera) - Liao, Ling-Hsiu (Insects, 2017)
Because certain flavonols and phenolic acids are found in pollen and nectar of most angiosperms, they are routinely ingested by Apis mellifera, the western honey bee. The flavonol quercetin and the phenolic acid p-coumaric acid are known to upregulate detoxification enzymes in adult bees; their presence or absence in the diet may thus affect the toxicity of ingested pesticides. We conducted a series of longevity assays with one-day-old adult workers to test if dietary phytochemicals enhance longevity and pesticide tolerance. One-day-old bees were maintained on sugar syrup with or without casein (a phytochemical-free protein source) in the presence or absence of quercetin and p-coumaric acid as well as in the presence or absence of two pyrethroid insecticides, bifenthrin and β-cyfluthrin. Dietary quercetin (hazard ratio, HR = 0.82), p-coumaric acid (HR = 0.91) and casein (HR = 0.74) were associated with extended lifespan and the two pyrethroid insecticides, 4 ppm bifenthrin (HR = 9.17) and 0.5 ppm β-cyfluthrin (HR = 1.34), reduced lifespan. Dietary quercetin enhanced tolerance of both pyrethroids; p-coumaric acid had a similar effect trend, although of reduced magnitude. Casein in the diet appears to eliminate the life-prolonging effect of p-coumaric acid in the absence of quercetin. Collectively, these assays demonstrate that dietary phytochemicals influence honey bee longevity and pesticide stress; substituting sugar syrups for honey or yeast/soy flour patties may thus have hitherto unrecognized impacts on adult bee health.